2014
DOI: 10.1002/ccd.25627
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcome from an all‐comers population of patients with ST‐segment elevation myocardial infarction treated with biolimus‐eluting stent with biodegradable polymer

Abstract: In a real-world cohort of STEMI patients undergoing PCI, the use of BES is associated with good 1-year clinical outcome. These results confirm and expand previous findings showing the efficacy and safety of BES in the setting of randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The Comparison of Biolimus Eluted From an Erodible Stent Coating With Bare‐Metal Stents in Acute ST‐Elevation Myocardial Infarction (COMFORTABLE AMI) trial involving 1161 patients subsequently showed for biodegradable‐polymer BES a lower risk of the 1 year composite primary endpoint of cardiac death, target‐vessel MI, and TLR (4.3% vs 8.7%, P = 0.004) . These findings were further supported in a real‐world multicenter registry of 311 patients showing a 3.4% rate of MACE (composite of cardiac death, recurrent MI, and ischemia‐driven TVR) at 1 year follow‐up .…”
Section: Discussionmentioning
confidence: 76%
“…The Comparison of Biolimus Eluted From an Erodible Stent Coating With Bare‐Metal Stents in Acute ST‐Elevation Myocardial Infarction (COMFORTABLE AMI) trial involving 1161 patients subsequently showed for biodegradable‐polymer BES a lower risk of the 1 year composite primary endpoint of cardiac death, target‐vessel MI, and TLR (4.3% vs 8.7%, P = 0.004) . These findings were further supported in a real‐world multicenter registry of 311 patients showing a 3.4% rate of MACE (composite of cardiac death, recurrent MI, and ischemia‐driven TVR) at 1 year follow‐up .…”
Section: Discussionmentioning
confidence: 76%
“… 23 Among patients with ST-segment-elevation MI undergoing primary PCI, BES was as sociated with a low incidence of 1-year MACE (3.2%) and also continued to improve cardiovascular events, compared with BMS beyond 1 year. 24 25 AMI subgroup analysis of the LEADER trial also showed BES, compared with SES, significantly improved 5-year safety and efficacy outcomes in patients with AMI (18.2% vs. 25.9%, p =0.025). 26 Our study will extend the follow-up period of the enrolled patients to 5 years to assess the long-term clinical outcomes of BES in Korean patients with ACS.…”
Section: Discussionmentioning
confidence: 93%
“…Only some small studies compared new‐generation BES versus EES/ZES. For instance, Tomai et al noticed that BES was associated with a good 1‐year clinical outcome in a real‐world STEMI cohort . Adriaenssens et al in their small preliminary series demonstrated no difference in the incidence of ST and overall MACE at 9‐months despite the significantly higher percentage of uncovered struts after bioresorbable‐polymer‐BES versus EES as assessed by OCT in the setting of ACS .…”
Section: Discussionmentioning
confidence: 99%